Sports haematology - Shaskey, D. J.; Green, G. A. (Sports Medicine, 2000)
While the crucial role of haemoglobin in aerobic exercise has been well accepted, there is still a great deal of controversy about the optimal haematological parameters in the athletic population. The initial part of this review will examine the question of anaemia in athletes. The most common finding in athletes is a dilutional pseudoanaemia that is caused by a plasma volume expansion, rather than an actual blood loss. It is not a pathological state and normalises with training cessation in 3 to 5 days. This entity should be distinguished from conditions associated with lowered blood counts, such as intravascular haemolysis or iron deficiency anaemia. The evaluation of true anaemia states in the athlete must take into account not only blood losses secondary to exercise, such as foot strike haemolysis or iron losses through sweat, but non-athletic causes as well. Depending on the age and sex of the athlete, consideration must be given to evaluation of the gastrointestinal or genitourinary systems for blood loss. Finally, a comprehensive nutritional history must be taken, as athletes, especially women, are frequently not consuming adequate dietary iron. The second section of the paper will deal with the very contentious issue of sickle cell trait. While there have been studies demonstrating an increased risk of sudden death in people with sickle cell trait, it is still quite rare and should not be used as a restriction to activity. Further, studies have demonstrated that patients with sickle cell trait have an exercise capacity that is probably normal or near normal. However, in the cases of sudden death, it has been secondary to rhabdomyolysis occurring among sickle cell trait athletes performing at intense exertion under hot conditions, soon after arriving at altitude. The recommendations are that athletes with sickle cell trait adhere to compliance with the general guidelines for fluid replacement and acclimatisation to hot conditions and altitude. The final section of the paper examines the issue of haematological manipulation for the purposes of ergogenic improvement. Although experiments with blood doping revealed improvements in running time to exhaustion and maximal oxygen uptake, the introduction of recombinant erythropoietin has rendered blood doping little more than a historical footnote. However, the improvements in performance are not without risk, and the use of exogenous erythropoietin has the potential for increased viscosity of the blood and thrombosis with potentially fatal results. Until a definitive test is developed for detection of exogenous erythropoietin, it will continue to be a part of elite athletics.